Dual careers as sustainable careers for performing artists in times of crisis. A contextual approach to the construct of a sustainable arts career. - Patrycja Mizera-Pęczek; Anna Krasnova; Magdalena Sasin; Aleksandra Sieczych-Kukawska (PLoS ONE)
For an individual, a sustainable career is a sequence of events in one's professional life that both brings professional satisfaction to the career actor, but also allows them to stay healthy, fit, satisfied with their non-work life, feel stable and secure, and free to decide their professional future. It is challenging to pursue a career as a performing artist in such a way that the artist can say of their career that it is sustainable. Indeed, research shows that artists struggle with job instability, being paid below expectations, high competition for lucrative career opportunities and the loss of psycho-physical fitness, which is important in the profession. Dual career is one of the paths for artists to build a conscious sustainable career. Inspired by research on dual careers for athletes, we found many similarities between the sport and artistic settings, mainly related to the short-term nature of these professions. The idea of an artist pursuing a dual career in such a way that they start preparing for an alternative career path already during their artistic training seems to be a potentially attractive career management strategy to facilitate career reorientation. This study investigates the opinions of performing artists regarding the opportunities to pursue a sustainable career through conscious preparation for career reorientation. A total of 111 performers from Poland participated in the survey. Assessments of the situation of artists in the labour market during the pandemic crisis, their attitudes towards the end/descent of their artistic careers, their opinions on alternatives to practising as a performing artist, and their assessments of the potential for pursuing a dual career strategy were investigated. The survey revealed that the opinions of artists are diverse and ambiguous, probably due to the internal diversity of this professional community. Importantly, a significant group of respondents in our survey said that it was the pandemic that made them aware of the instability of a career as a performing artist (56.7%). The analysis of the research results shows what career self-management strategies the respondents use. Remarkably, for a group of respondents, the pandemic crisis has become a determinant for taking steps towards sustainable career management.